Masada : from Jewish revolt to modern myth - Magness, Jodi (Princeton University Press, 2019)
A new account of the famous site and story of the last stand of a group of Jewish rebels who held out against the Roman Empire. Two thousand years ago, 967 Jewish men, women, and children-the last holdouts of the revolt against Rome following the fall of Jerusalem and the destruction of the Second Temple-reportedly took their own lives rather than surrender to the Roman army. This dramatic event, which took place on top of Masada, a barren and windswept mountain overlooking the Dead Sea, spawned a powerful story of Jewish resistance that came to symbolize the embattled modern State of Israel. The first extensive archaeological excavations of Masada began in the 1960s, and today the site draws visitors from around the world. And yet, because the mass suicide was recorded by only one ancient author-the Jewish historian Josephus-some scholars question if the event ever took place. Jodi Magness, an archaeologist who has excavated at Masada, explains what happened there, how we know it, and how recent developments might change understandings of the story. Incorporating the latest findings, she integrates literary and historical sources to show what life was like for Jews under Roman rule during an era that witnessed the reign of Herod and Jesus's ministry and death. Featuring numerous illustrations, this is an engaging exploration of an ancient story that continues to grip the imagination today.